Author Correction: The global distribution of tetrapods reveals a need for targeted reptile conservation. Issue 1 (January 2018) - Roll, Uri; Feldman, Anat; Novosolov, Maria; Allison, Allen; Bauer, Aaron; Bernard, Rodolphe; Böhm, Monika; Castro-Herrera, Fernando; Chirio, Laurent; Collen, Ben; Colli, Guarino; Dabool, Lital; et al.
In the version of this Article originally published, grant no. 2015/20215-7 for C.N. was omitted from the Acknowledgements section. This has now been corrected in all versions of the Article.